2021
DOI: 10.3390/ma14227069
|View full text |Cite
|
Sign up to set email alerts
|

Brewed Robusta Coffee Increases Nickel Ion Release from Dental Alloys: An In Vitro Study

Abstract: Alloys in oral cavity always interact with dynamic oral environment, such as pH, temperature, salivary conditions, and dietary habits. Coffee can further decrease pH in the oral cavity. Thus, coffee may increase the release of metal ions that may lead to various health diseases. This study aimed to quantitively investigate the effect of brewed Robusta coffee on the nickel ion release and their morphological structures; Methods: 20 alloy specimens were divided into 4 groups and placed in solutions for 48 and 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Shahabi et al showed that frequent intake of acidic products may significantly increase the corrosion of orthodontic brackets [ 145 ]. Recently, the effect of brewed coffee may increase ion release from nickel titanium alloy due to the decreased pH of saliva mixed with coffee [ 146 ]. Conversely, Parenti et al detected in vitro no effect of acidic beverages on the surface structure of nickel-titanium orthodontic archwires [ 147 ].…”
Section: Factors Affecting the Risk Of Dental Alloys Side Effectsmentioning
confidence: 99%
“…Shahabi et al showed that frequent intake of acidic products may significantly increase the corrosion of orthodontic brackets [ 145 ]. Recently, the effect of brewed coffee may increase ion release from nickel titanium alloy due to the decreased pH of saliva mixed with coffee [ 146 ]. Conversely, Parenti et al detected in vitro no effect of acidic beverages on the surface structure of nickel-titanium orthodontic archwires [ 147 ].…”
Section: Factors Affecting the Risk Of Dental Alloys Side Effectsmentioning
confidence: 99%